Penentuan Rute Pengangkut Limbah Medis Optimal Menggunakan Vehicle Routing Problem with Time Window pada Kasus Multi Depot - Erika Fatma; Winanda Kartika; Aniza Nur Madyanti (Jurnal Manajemen dan Organisasi, 2022)
The current COVID-19 pandemic has created new environmental problems. The increase of medical waste due to increased activity in public health facilities is a new threat to environmental health. Unfortunately, not all health facilities have the capacity to manage their own waste. This causes the medical waste need to be taken to a waste treatment center for proper treatment that meets environmental health standards. Reverse logistics is one of the activities that can help the process of transporting medical waste. This study uses a vehicle routing problem with a time window (VRPTW) for multi depot cases. The limitations used in this study are the operational time of each Puskesmas, vehicle capacity and operational working hours of waste transport officers. In this case, the optimization of the cost calculation for the transportation of waste from 42 health centers in the DKI Jakarta area is carried out to be taken to three central locations for waste treatment. The purpose of the model used is to minimize transportation costs, namely fixed costs and variable costs of the vehicle used. The routes generated from this research are six transportation routes with a total distance of 412,31 km, with a total cost of Rp 5.928.498,75.